The Impact of Megaprojects on Branding Ethiopia as an Appealing Tourist Destination - GIRMA, Mulugeta; SINGH, Manjit (Journal of Environmental Management and Tourism, 2019)
The purpose of this paper is to analyze the impact of megaprojects on a destination branding and then proceeds to examine cognitive, affective and unique image and their significance as perceived by tourists. A multi stage sample of 400 external publics was surveyed. Factor analysis together with SEM is used and tested whether and how much the influencing factors predicted a significant amount of the variance in travel. The result shows Megaprojects have largest significant effect on cognitive, affective and unique image development. And there is a strong relationship between mega infrastructural facilities development and perceived destination image.